Slow-Release H2S Donor Anethole Dithiolethione Protects Liver From Lipotoxicity by Improving Fatty Acid Metabolism - Zhao, Chengcheng; Yu, Nannan; Li, Wenqun; Cai, Hualin; Liu, Mouze; Hu, Yanjie; Liu, Yiping; Tang, Mimi (Frontiers in Pharmacology, 2020)
"Lipotoxicity" induced by free fatty acids (FAs) plays a central role in the pathogenesis of many metabolic diseases, with few treatment options available today. Hydrogen sulfide (H2S), a novel gaseous signaling molecule, has been reported to have a variety of pharmacological properties, but its effect on FAs metabolism remains unclear. The purpose of this study was to investigate the effect and mechanisms of anethole dithiolethione (ADT, a sustained-release H2S donor) on hepatic FAs metabolism. ADT was administered daily for 4 weeks in male Syrian golden hamsters fed a high fat diet (HFD), and FAs profiles of liver tissues were analyzed using GC-MS. The results showed that in HFD-fed hamsters, ADT treatment significantly reduced the accumulation of toxic saturated and monounsaturated fatty acids (C16:0, C18:0, C16:1, and C18:1n9), while increased the content of n-6 and n-3 series polyunsaturated fatty acids (C20:3n6, C20:4n6, and C22:6n3). Mechanistically, ADT obviously inhibited the overexpression of ACC1 (Acetyl-CoA carboxylase1), FAS (Fatty acid synthase) and SCD1 (Stearoyl-CoA desaturase1), and up-regulated the levels of FATPs (Fatty acid transport proteins), L-FABP (Liver fatty acid binding protein), CPT1α (Carnitine palmitoyltransferase 1α), FADS1 and FADS2 (Fatty acid desaturase). Notably, ADT administration significantly promoted Mitofusin1-mediated mitochondrial fusion and fatty acid β-oxidation. These findings suggest that ADT plays a beneficial role by regulating the synthesis, desaturation, β-oxidation, uptake, binding/isolation, and transport of FAs. In conclusion, ADT is effective in improving FAs metabolic disorders and liver injuries caused by HFD, which renders ADT a candidate drug for lipotoxicity-induced diseases.